2009
DOI: 10.1111/j.1476-5829.2008.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor receptor and vascular endothelial growth factor in malignant canine epithelial nasal tumours*

Abstract: Epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) signalling pathways play a role in carcinogenesis. Inhibition of EGF receptor (EGFR) and of VEGF is effective in increasing the radiation responsiveness of neoplastic cells both in vitro and in human trials. In this study, immunohistochemical evaluation was employed to determine and characterize the potential protein expression levels and patterns of EGFR and VEGF in a variety of canine malignant epithelial nasal tumours. Of 24 maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
(52 reference statements)
2
38
0
4
Order By: Relevance
“…As a result of the research, evaluation of the expression of VEGF and its receptors was demonstrated to be a reliable prognostic factor in squamous cell carcinoma of the oral cavity and tongue in humans, as well as in those of the oral cavity and nasal epithelium in dogs. Owing to this, the development and local recurrence as well as the formation of distant metastases can be monitored (Smith et al, 2000;López de Cicco et al, 2004;Shiomitsu et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…As a result of the research, evaluation of the expression of VEGF and its receptors was demonstrated to be a reliable prognostic factor in squamous cell carcinoma of the oral cavity and tongue in humans, as well as in those of the oral cavity and nasal epithelium in dogs. Owing to this, the development and local recurrence as well as the formation of distant metastases can be monitored (Smith et al, 2000;López de Cicco et al, 2004;Shiomitsu et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Expression of its receptor was observed in most studied cases of squamous skin cancers in cats -it correlated with shorter life expectancy but not with the tumour's mitotic activity (29). Incorrect activation of the EGFR receptor was also identified in epithelial tumours with high metastatic potential located in the lungs, nasal cavity and mamma in dogs (30)(31)(32) and oral cavity in cats (33).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies have made it possible to use the expression of VEGF and its receptors as a significant prognostic factor in cases of SCC of the oral cavity in humans as well as SCC of the oral cavity and nasal epithelium in animals. Thus it is possible to monitor the development and local relapse of the disease, as well as the incidence of distant metastases (19).…”
Section: Resultsmentioning
confidence: 99%